Practical bamboo joint design for small bamboo shelter - Ali Marzuki Ab Rani (2012)
This report is focused on the analysis of displacement of bamboo X – joints under compressive load. Two different designs were conceptualized based on results obtained by previous final year project (FYP) students who reinforced the X – Joint using galvanized steel plate (Ng, 2010) and bolt (Ong, 2010).